Globalization, changing demographics, and educational challenges in East Asia - Hannum, Emily; Park, Hyunjoon; Butler, Yuko Goto. (Bingley, UK : Emerald, 2010)
In recent decades, globalization and regional integration have brought significant economic and demographic changes in East Asia, including rising economic inequality, growing population movements within and across borders, and the emergence or renewed geopolitical significance of cultural and linguistic minority populations. These trends have coincided with significant changes in family formation, dissolution, and structures. How have these changes played out in the diverse educational systems of East Asia? In what innovative ways are East Asian governments addressing the new demographic realities of their student populations? This volume offers a snapshot of key educational stratification issues in East Asian nations, and their evolution in conjunction with changing student populations. Ten empirical pieces address issues ranging from Japan's education reforms and changes in teacher work patterns as the system adapts to globalization; persisting and new forms of educational stratification in China; educational stratification and new multiculturalism in educational policy in Korea; and the ways that migration is shaping education in the city-states of Hong Kong and Singapore. Collectively, the pieces in this volume represent a first attempt to investigate national responses to critical regional trends.
Editors' introduction: emerging issues for educational research in East Asia / Emily Hannum, Hyunjoon Park and Yuko Goto Butler -- Part I: Globalization and educational response in Japan. The twisted unintended impacts of globalization on Japanese education / Takehiko Kariya and Jeremy Rappleye ; Educational reform, academic intensity, and educational opportunity in Japan / Christopher Bjork -- Part II: Curricular innovation and the evolution of inequality in China. State-sponsored knowledge for the global age: global and traditional values in the Chinese language arts curriculum / Tanja Carmel Sargent and Xiao Yang ; Changes in educational inequality in China, 1990-2005 : evidence from the population census data / Xiaogang Wu and Zhuoni Zhang -- Part III: Educational disparities and multicultural education policy in Korea. Educational inequality in South Korea: the widening socioeconomic gap in student achievement / Soo-yong Byun and Kyung-keun Kim ; Policy note: diversification of the student population and multicultural educational policies in Korea / Youngdal Cho -- Part IV: Migration and education in the city-states of East Asia. The educational progress of mainland Chinese immigrant students in Hong Kong / Suet-ling Pong and Wing Kwong Tsang ; Postsecondary educational expansion and social integration in Hong Kong / David Post ; 'Downed' and stuck in Singapore: lower/middle class South Korean wild geese (kirogi) children in Singapore / Jeehun Kim.
Description based on print version record.
Includes bibliographies.
Print version record
Keywords: Globalization -- Social aspects; Educational change -- Japan; Educational change -- China; Educational change -- Korea (South); Educational change -- China -- Hong Kong; Educational change -- Singapore; Philosophy & theory of education; Sociology; Education -- Educational Policy & Reform -- General; Education -- Philosophy & Social Aspects; Education -- Research